Study of wine proteins by immunological methods. II -Evidence for structural similarity amongst the major wine proteins and structural dissimilarity with Chitinase and Thaumatin - Pereira, M.A.P. (2013)
Proceedings of a conference held in Mragowo Poland, from the 18th to 20th may, 1998, under the title "Structure and Functionality of Food Products".